Jhakar - Amira, Alam (book group Karachi, 2006)
Jhakar is a story about a big storm. The storm is waiting for dark clouds to gather before it can show its power. When the clouds come together, the storm starts to rage. It brings strong winds and heavy rain. This story is about the power of nature and how it can affect our lives.